Recursos Avaliativos nas crenças de professores de língua inglesa sobre aspectos de sua atuação pedagógica - Vieira, Cristiane Rodrigues (2019)
Beliefs are ways of thinking that help to build the reality and the perception that human beings have of the world around them. Teachers´ beliefs have been subject of study in lots of research in the field of Applied Linguistics since the 1990s (ALVAREZ, 2007; BONFIM; CONCEIÇÃO, 2009; MEIRELES; FERREIRA, 2010; OLIVEIRA, 2011; PERINE, 2012; ZOLNIER, 2012, among others) and have contributed to the comprehension of activities teachers carry out in their classrooms, as well as to their decision making which can influence in a positive or negative way the teaching and learning as well. The aim of this research is to describe how, in their beliefs, English teachers, Language and Literature Graduates - Portuguese and English - from the Regional University of Cariri, evaluate themselves about aspects of their pedagogical performance. To attain such an objective, I conducted an exploratory and descriptive research with qualitative analysis in order to (1) find out how the evaluative lexicogrammatical realizations in the English teachers´ beliefs reveal their evaluative positionings about themselves as English teachers, (2) verify how the evaluative lexicogrammatical realizations in the English teachers´ beliefs show their evaluative positionings about their profession and (3) identify how evaluative lexicogrammatical realizations in the English teachers´ beliefs indicate their evaluative positionings about their students´ learning. Fifteen teachers from public schools and public universities answered an online questionnaire about beliefs they had about themselves as English teachers, about their profession and about their students´ learning of English. The analysis was carried out considering the orientations of Kalaja (1995) and Barcelos (2001) on how to identify the beliefs and by means the Appraisal System categories (MARTIN; WHITE, 2005). The results showed that the positive evaluations about the three beliefs overcame the negative ones. Most teachers like their profession and consider it important, evaluate themselves as competent and believe they can change the personal and professional reality of their students. They believe that the students can learn the taught contents, although it is necessary to extent knowledge to all language skills, which has not happened yet due to external factors such as few classes per week and lack of interest on the part of the students.